Evolution of jewelry art in Kazakhstan: traditions and modern trends - K. B. Monakhova; V. Ivanova (Nomadic Civilization: Historical Research)
National jewelry is an important element of the cultural heritage of any country, which reflects the history and traditions of the people, its uniqueness, embodying craftsmanship and the inextricable link between generations. They serve not only as decorations in a person’s daily life, but also as a symbol of national identity. The article examines the historical path of jewelry art in Kazakhstan, starting from ancient times and ending with its modern trends. It describes the development of metalworking technologies, the use of various materials by nomadic peoples, including metal, bones, stones and wood, to create unique products and the influence of culture on their design. Preservation of cultural sovereignty is an important task for ensuring national identity and sustainable development of any country, therefore, special attention is paid to the importance of jewelry as an element of national heritage and their role in strengthening the identity of the Kazakh people. In parallel, modern trends and prospects for the development of national jewelry art in the context of globalization are analyzed. This study is based on the analysis of historical sources, archaeological finds, including their modern interpretation, as well as interviews with modern masters in the jewelry industry, which allows us to give a comprehensive assessment of the cultural and artistic value of Kazakh jewelry traditions.